PERWUJUDAN PERLINDUNGAN TERHADAP KORBAN CYBER FLASHING ATAS KEKERASAN GENDER SECARA ONLINE - Salsabila Salsabila; Adhitya Widya Kartika (LPPM Universitas Ekasakti Padang, 2023)
Cyber Flashing is a form of Online Gender-Based Violence (KBGO) which is carried out by perpetrators by sending pictures and/or video messages of genitals or things that have sexual content to other people without the consent of the recipient of the message. This study aims to explore Law no. 12 of 2022 concerning Crimes of Sexual Violence which at least can be a hope for victims to get justice and legal protection, one of which is by the threat of punishment as stated in Article 14. The authors in this study used a type of normative juridical research with a statutory, theoretical, and legal approach. and cases. The results of this study are that the legal protection that is obtained by victims of sexual violence, especially those that occur on social media such as Cyber ​​Flashing, cannot be carried out optimally because derivative regulations have not been issued and several obstacles make victims not dare to report them to the parties. the authorities which results in hampering efforts to enforce the law on acts of sexual violence.